(untitled) (Global Journal of Management and Business Research, 2016)
The paper questions the ability of arbitrageurs to ascertain value with some confidence and to realize it quickly. The discussion in the paper suggests a reason why some markets are more attractive for arbitrage than others The paper identifies a number of so-called anomalies in which particular investment strategies have may not earn higher returns than their systematic risk. Our analysis offers a different mathematical approach to understanding these anomalies than does the standard efficient market theory.